El servicio de transporte público urbano en la ciudad de Loja y su incidencia en la satisfacción ciudadana, en el primer semestre del año 2021 - Castillo Pesántez, Gabriela Alexandra (2022)
The present research work aims to determine the quality of urban public transportation service in Loja city, and its impact on the level of users satisfaction from their perspective. The study was based on a mixed approach with a descriptive, non-experimental and cross-sectional scope. An observation sheet, interviews were the authorities in charge of public transport services, considering the parameters of the Manual for the Implementation of Quality Indicators for Public Transport Service Quality in the Metropolitan District of Quito, and a survey based on the Servperf model with 22 items based on five dimensions: tangible elements, reliability, responsiveness, safety, and empathy applied to 120 users. The results revealed the main shortcomings, such as lack of coordination and institutional communication for decision- making between the City Hall and the Consortium; poorly trained personnel in transportation issues; lack of constant road maintenance; and inadequate signage at the city's bus stops. As for the quality level, an overall average of 55% was found, qualified as neither agreeing nor disagreeing with the service, and from the citizen's perspective, according to the averages of the Servperf model items, a satisfaction level of 54.39% was found, reflecting that the user partially disagrees with the service provided. For this reason, a proposal was designed to improve the public transportation service from an institutional and user's point of view to order to increase the quality of the service and the level of citizen satisfaction.